Performance and Instability of Oilseed Crops in Pakistan - Muhammad Nisar Khan; Arshad Mahmood Malik; Faheem Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
This comprehensive study spanning from 1971-72 to 2021-22 consistently discerned distinct patterns of variability and instability within Pakistan's oilseed crops. Analyzing instability in the cultivation area, yield, and production of oilseed crops is crucial for effective planning and strategy formulation. The study encompasses the analysis of nine oilseed crops, namely cotton, rapeseed-mustard (including canola), sesame, groundnut, sunflower, castor seed, linseed, soybean, and safflower. The Coefficient of Variation (CV) and the Cuddy-Della Valle Instability Index (CDVI) were employed to assess fluctuations and instability in the cultivation area, production, and yield of these crops. The findings highlighted that cotton exhibited a high degree of instability in production and yield, while rapeseed-mustard (including canola) consistently displayed a high degree of production volatility, underscoring the critical need for a sustainable and steady supply of these commodities. Sesame output revealed frequent instability, demanding prompt and effective mitigation actions. Groundnut production consistently demonstrated mild inconsistency, emphasizing the need for vigilant monitoring to ensure supply stability. Sunflower cultivation faced substantial insecurity, necessitating comprehensive stabilization techniques. Soybean production continually grappled with significant insecurity across all factors, emphasizing the importance of robust risk management. Safflower production consistently posed challenges due to extreme instability, requiring ongoing solutions. Linseed regularly manifested moderate instability, indicating room for improvement with better management. Castor seed production showed considerable volatility in cultivation area and production but low yield instability, underscoring the significance of targeted stability solutions. Addressing insecurity in Pakistan's oilseed crop sectors is crucial for food security, requiring proactive measures like improved forecasting, resource allocation, and informed policy-making for long-term stability.